Peer Review of Teleradiology at a Teleradiology Clinic: Comparison of Unacceptable Diagnosis and Clinically Significant Discrepancy between Radiology Sections and Imaging Modalities - Hyung Suk Seo (The Korean Society of Radiology, 2021)
Purpose The purpose of this study was to evaluate the rates of unacceptable diagnosis and clinically significant diagnostic discrepancy in radiology sections and imaging modalities through a peer review of teleradiology. Materials and Methods Teleradiology peer reviews in a Korean teleradiology clinic in 2018 and 2019 were included. The peer review scores were classified as acceptable and unacceptable diagnoses and clinically insignificant and significant diagnostic discrepancy. The diagnostic discrepancy rates and clinical significance were compared among radiology sections and imaging modalities using the chi-square test. Results Of 1312 peer reviews, 117 (8.9%) cases had unacceptable diagnoses. Of 462 diagnostic discrepancies, the clinically significant discrepancy was observed in 104 (21.6%) cases. In radiology sections, the unacceptable diagnosis was highest in the musculoskeletal section (21.4%) (p < 0.05), followed by the abdominal section (7.3%) and neuro section (1.3%) (p < 0.05). The proportion of significant discrepancy was higher in the chest section (32.7%) than in the musculoskeletal (19.5%) and abdominal sections (17.1%) (p < 0.05). Regarding modalities, the number of unacceptable diagnoses was higher with MRI (16.2%) than plain radiology (7.8%) (p < 0.05). There was no significant difference in significant discrepancy. Conclusion Peer review provides the rates of unacceptable diagnosis and clinically significant discrepancy in teleradiology. These rates also differ with subspecialty and modality.